PREDICTION OF SETTLEMENT AND LAND USE CHANGES ON MANSINAM ISLAND FROM 2025 TO 2031 USING THE CELLULAR AUTOMATA SIMULATION METHOD - Valderama, Aldi Fariz; Taplo, Yulianto; Riansyah, Ardi; Habibi, Syavitra L. P.; Siagian, Adi Frianda; Popoi, Taufik Syahrul; Nasir, Muh. Irwana Segara; Iba, Amos; Laitupa, Karmila (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
Indonesia, as an archipelagic country, faces development challenges on its small islands, including Mansinam Island. This study aims to predict settlement and land cover changes on Mansinam Island for the period 2025–2031. The data used were surface reflectance-corrected Sentinel-2 imagery with a spatial resolution of 10 meters. The imagery was acquired in 2019, 2022, and 2025. Land cover classification was performed using a supervised classification method with the minimum distance algorithm, achieving an accuracy of 87.82%. Land change prediction modeling was carried out through land use change analysis and simulation using the Cellular Automata (CA) and Artificial Neural Network-Cellular Automata (ANN-CA) models. The model produced a Percent of Correctness of 89.96%. The simulation results indicate that from 2025 to 2031 there will be no significant land change, with transformed land areas of 43.85 ha in 2025, 42.62 ha in 2028, and 42.64 ha in 2031. The results also show that the development rate on Mansinam Island tends to slow down.